Model peptides containing the 3-sulfanyl-norbornene amino acid, a conformationally constrained cysteine analogue effective inducer of 310-helix secondary structures1. Issue 41 (7th May 2015) - Ruffoni, Alessandro; Contini, Alessandro; Soave, Raffaella; Lo Presti, Leonardo; Esposto, Irene; Maffucci, Irene; Nava, Donatella; Pellegrino, Sara; Gelmi, Maria Luisa; Clerici, Francesca
<x xml:space="preserve">Abstract</x> Two model peptides containing the 3-benzylsulfanylnorbornene amino acid (NRB) was prepared. Theoretical calculations, spectroscopic and X-ray analyses confirmed that both NRB enantiomers possess a strong right-handed helicogenic effect.